2013
DOI: 10.1007/s10535-012-0294-9
|View full text |Cite
|
Sign up to set email alerts
|

Allelic differentiations and effects of the Rf3 and Rf4 genes on fertility restoration in rice with wild abortive cytoplasmic male sterility

Abstract: To reveal the allelic differentiations at the two genes for fertility restoration (Rf) on chromosomes 1 (Rf3) and 10 (Rf4), 15 chromosome single segment substitution lines (SSSLs) with the Rf3 locus and 18 SSSLs with the Rf4 locus were crossed with Bobai A (BbA), a cytoplasmic male sterility line with wild abortive type of cytoplasm (WA-CMS), respectively. Based on the pollen and seed fertility of the F 1 hybrids, the Rf3 and Rf4 genes were each classified into four alleles, namely Rf3-1, Rf3-2, Rf3-3, and Rf3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 31 publications
4
25
0
Order By: Relevance
“…Cai et al. () also reported similar results where the IR64 (effective restorer) carrying Rf3Rf4 alleles and Basmati 370 (partial restorer) carrying rf3Rf4 alleles showed 85.4% and 59.3% spikelet fertility, respectively. The analysis of variance among the four groups ( rf3rf4, Rf3Rf4, Rf3rf4 and rf3Rf4 ) pooling WA and Kalinga CMS‐based F 1 populations showed significant differences revealing the occurrence of substantial variability of spikelet fertility restoration due to different Rf allele combinations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Cai et al. () also reported similar results where the IR64 (effective restorer) carrying Rf3Rf4 alleles and Basmati 370 (partial restorer) carrying rf3Rf4 alleles showed 85.4% and 59.3% spikelet fertility, respectively. The analysis of variance among the four groups ( rf3rf4, Rf3Rf4, Rf3rf4 and rf3Rf4 ) pooling WA and Kalinga CMS‐based F 1 populations showed significant differences revealing the occurrence of substantial variability of spikelet fertility restoration due to different Rf allele combinations.…”
Section: Discussionsupporting
confidence: 89%
“…Further, presence of same functional WA352 gene indicated the common mechanism of fertility restoration in both the CMS. The greater genetic association of Rf4 as compared to Rf3 in WA CMS has also been reported earlier (Yao et al 1997, Zhuang et al 2001, Ahmadikhah and Karlov 2006, Sattari et al 2008and Cai et al 2013). Cai et al (2013) also reported similar results where the IR64 (effective restorer) carrying Rf3Rf4 alleles and Basmati 370 (partial restorer) carrying rf3Rf4 alleles showed 85.4% and 59.3% spikelet fertility, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…Similar results were reported for WA-type CMS in that the effect of Rf4 appeared to be larger than that of Rf3 and inheritance of both Rf genes resulted in compounded effects [18, 46, 48, 49]. The mitochondrial gene WA352 was recently described in wild rice and is associated with WA-, ID-, and DA-type CMS, suggesting that Rf3 ( qRf1.1 ) and Rf4 ( qRf10.2 ) are effective for restoring the fertility of DA-, ID-, and WA-type CMS [8].…”
Section: Discussionsupporting
confidence: 79%
“…The hybrids produced using converted Swarna breeding lines with Rf3 gene showed 15-20% of more pollen and spikelet fertility than the partial restorer Swarna. This clearly demonstrates that that Rf3 gene may be contributing 15 to 30% for the fertility restoration trait of WA-CMS and Rf4 may be contributing about 70% for the same trait and presence of both the genes can bestow complete fertility restoration 13,[33][34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 99%